Dual-Gradient Impedance/Insulation Structured Polyimide Nonwoven Fabric for Multi-Band Compatible Stealth - Tang, Xinwei; Hong, Wei; Hong, Wei; Gao, Hongmiao; Li, Shuangshuang; Li, Wei; Lai, Kaixin; Xu, Mingzhen; Hu, Zaiyin; Li, Yan; Wang, Zicheng; Liu, Tianxi (Nano-Micro Letters, 2026)
Designing and preparing a compatible electromagnetic interference (EMI) shielding, radar and infrared stealth material exhibits significant prospect in the military field. Hence, a novel conductive/magnetic polyimide-based nonwoven fabric (PFNy) is prepared by alkali treatment, Fe3+ ion exchange, thermal reduction, and electroless nickel (Ni) plating process. Its impedance/insulation characteristics can be easily adjusted by controlling the in situ growth of Fe3O4 and electroless nickel plating. Subsequently, a new strategy of constructing hierarchical dual-gradient impedance/insulation structure is implemented to achieve EMI shielding, radar and infrared stealth via stacking PFNy with gradually decreased impedance/insulation characteristics from top to bottom. The formation of impedance matching gradient structure promotes effective introduction and dissipation of electromagnetic waves, endowing the composite with outstanding EMI shielding and radar stealth performance. Meanwhile, the construction of thermal insulation gradient structure can effectively inhibit thermal radiation from target, bringing an excellent infrared stealth performance. Importantly, the strong interfacial interactions between Fe3O4, Ni and polyimide fiber accelerate PFNy to resist the stresses originated from high-temperature heat source, achieving a compatible high-temperature resistant radar/infrared stealth performance. Such excellent comprehensive properties endow it with a great potential in high-temperature military camouflage applications against enemy radar and infrared detection. Highlights: 1 A novel conductive/magnetic polyimide nonwoven fabric is prepared by alkali treatment, Fe3+ ion exchange, thermal reduction, and electroless nickel plating process. 2 Dual-gradient impedance/insulation structure is assembled through stacking different conductive/magnetic polyimide nonwoven fabrics with gradually decreased impedance/insulation characteristic from top to bottom. 3 The strong interfacial interaction and dual-gradient impedance/insulation structure bring a compatible electromagnetic interference shielding, high-temperature resistant radar and infrared stealth performance.